THE EFFECT OF ROOM TEMPERATURE ON THE LEARNING CONCENTRATION OF PSYCHOLOGY STUDENTS IN CLASS PI3 OF UIN RADEN FATAH PALEMBANG - Ramadhani, Wanda Aulia; Puji Safitri; R.A Maryam; Annisa Artha Yunia; Salwa Miftahul Jannah; Cindy Ramadhanty (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
The purpose of this study was to determine the effect of room temperature on the learning concentration of psychology students in class PI3. This research was conducted at the Psychology Faculty of Raden Fatah University, Palembang, with a sample of all students of the PI3 class of the psychology faculty. The method used in this research is quantitative with a quasi-experimental research type. The research design used is static group design. The data analysis of this study used an unpaired sample t-test, namely the independent sample t-test. The results of this study indicate that the value of sig. (2-tailed) obtained is 0.000 <0.05 so it can be concluded that H0 is accepted. So it can be said that the room temperature has an influence on the concentration of studying psychology students in the PI3 class of the State Islamic University of Raden Fatah, Palembang.